Exorcising the Exocyst Complex - Heider, Margaret R. (2012)
The exocyst complex is an evolutionarily conserved multisubunit protein complex implicated in tethering secretory vesicles to the plasma membrane. Originally identified two decades ago in budding yeast, investigations using several different eukaryotic systems have since made great progress toward determination of the overall structure and organization of the eight exocyst subunits. Studies point to a critical role for the complex as a spatiotemporal regulator through the numerous protein and lipid interactions of its subunits, although a molecular understanding of exocyst function has been challenging to elucidate. Recent progress demonstrates that the exocyst is also important for additional trafficking steps and cellular processes beyond exocytosis, with links to development and disease. In this review, we discuss current knowledge of exocyst architecture, assembly, regulation and its roles in a variety of cellular trafficking pathways.